MODEL OF INFORMATION RISK MEASUREMENT IN CORPORATE SYSTEMS - H. Melnyk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The features and world experience of information risk management are analyzed. The necessity of a comprehensive approach to the analysis and management of information risks in corporate systems is proved. The economic-mathematical model was built with the application of the the-ory and tools of fuzzy sets and fuzzy logic, which can more accurately measure the risk of information and make effective decisions in reducing the risk of possible lost in the corporate systems.